ON THE RELATIONS BETWEEN CRATONIC LITHOSPHERE THICKNESS, PLATE MOTIONS, AND BASAL DRAG - Artemieva I.M.; Mooney W.D. (My University, 2002)
An overview of seismic, thermal, and petrological evidence on the structure of Precambrian lithosphere suggests that its local maximum thickness is highly variable (140–350 km), with a bimodal distribution for Archean cratons (200–220 km and 300–350 km). We discuss the origin of such large differences in lithospheric thickness, and propose that the lithospheric base can have large depth variations over short distances. The topography of Bryce Canyon (western USA) is proposed as an inverted analog of the base of the lithosphere.
Keywords: Continental lithosphere; Plate motions; Archean; Proterozoic; Lithosphere thickness